Covid-19 en Afrique: Études de cas sur la morbidité et la mortalité dans une perspective comparative - Michel Garenne (Fondation pour les études et recherches sur le développement international (FERDI), 2023)
– The study reviews the very fragmented data on Covid-19 morbidity and mortality in sub-Saharan Africa, and puts it into perspective with French and international data. Two Sahelian countries are studied in more detail: Burkina-Faso and Niger. Several seroprevalence surveys are reviewed, showing a rapid increase in the number of cases during the first 12 to 24 months of the epidemic. The cumulative incidence appears higher than in Europe during the same period. On the other hand, available data indicate fewer cases in 2022, unlike France and European countries. MSF/Epicentre mortality surveys are reviewed: in a refugee camp in Kenya and in three African towns, as well as a general population study in one province of South Africa. Despite their limitations, these studies show an increase in mortality following the emergence of SARS-CoV-2. But overall, case-fatality rates do not reveal severe mortalities in Africa. In addition, the very young age structure of African populations, with many children less affected and few very vulnerable elderly people, is in their favor, and leads to much lower standardized death rates than in France. Finally, if Covid-19 had negative economic impacts, these do not seem to translate into an increase in under- five mortality. If mortality by Covid-19 remains poorly known in Africa, nothing currently indicates a major demographic crisis.
Keywords: 330; Demographics; Covid-19; SARS-CoV-2; Mortality; Morbidity; Seroprevalence; South Africa; Burkina Faso; Niger